PENGARUH MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN FLIPPED CLASSROOM TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA DI MAN 2 MODEL MEDAN - Teti Damayanti; Rugaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine students' problem solving abilities and the effect of applying the problem based learning model with the flip classroom approach to energy source material in class X MAN 2 Medan Model. This type of research is quasi-experimental with a pretest-posttest control group design. The population in the study were all students of class X MAN 2 Model Medan. The sampling technique was carried out using a random sampling technique which consisted of two classes, namely the experimental class and the control class. The experimental class, namely class X-N, is taught using a problem based learning model with a flipped classroom approach, consisting of 32 students, while the control class, namely class The instrument used is a problem solving ability test in the form of an essay with 5 questions. The initial stage was to give a pretest to both classes. For the experimental class the average result was 48.06 and for the control class it was 44.00. After giving treatment to both classes, the researcher gave a posttest and the results obtained for the experimental class were 78.41, and for the control class it was 62.66. The resulting data was analyzed using the t statistical test. Based on the research results, it shows that: the average gain in problem solving abilities of students who are taught using the problem based learning model using the flipped classroom approach is better than just using the problem based learning model. This research concludes that the application of the problem based learning model with a flipped classroom approach is able to improve students' problem solving abilities on energy sources material.